Spatiotemporal evaporating droplet dynamics on fomites enhances long term bacterial pathogenesis - Sreeparna Majee (Nature Portfolio, 2021)
Sreeparna Majee et al. combines flow visualization, optical microscopy, mathematical modeling, and biological experiments to study the spatial and temporal dynamics of drying bacterial droplets, demonstrating long-term bacterial pathogenesis after drying and rehydration.